2020
DOI: 10.1111/ajt.16154
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Bluetooth tablet-based technology to improve outcomes in lung transplantation: A pilot study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Schenkel et al 38 used Bluetooth‐based tablet technology in their study and, using this technology, transmitted patient vital signs information and respiratory parameters to real‐time transplant coordinators to improve transplant results. The platform also enables the communication between patients and providers and includes a comprehensive tutorial library with custom video content and daily reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schenkel et al 38 used Bluetooth‐based tablet technology in their study and, using this technology, transmitted patient vital signs information and respiratory parameters to real‐time transplant coordinators to improve transplant results. The platform also enables the communication between patients and providers and includes a comprehensive tutorial library with custom video content and daily reports.…”
Section: Resultsmentioning
confidence: 99%
“…An important part of software development is quality evaluation. For example, user satisfaction is one of the evaluations that can be measured by examining the usability of the system 42 ; 37/5% of the studies did not have an application quality evaluation scale, 27 , 31 , 33 , 34 , 37 , 38 and 31/25% of the articles evaluated acceptability and usability. 7 , 28 , 29 , 30 , 40 Three studies used the PSSUQ or ASQ questionnaire for evaluation, 7 , 40 , 41 and the other studies used surveys and interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric oncology, a systematic review of 21 digital health interventions identified mixed evidence for effectiveness, but these studies suffered from several methodological limitations. 51 A recently published pilot study 52 investigating a remote monitoring intervention in adult lung transplant recipients determined they could be engaged long term (i.e., enter monitoring data at least weekly for approximately 2 years). Survival rates did not differ between the monitored and control groups, but in a retrospective review, the intervention was associated with lower hospital readmissions and as intended, the intervention addressed avoidance behaviors in patients and/or their caregivers, decreased distress, and increased medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…While wearable technologies have yet to be extensively used for monitoring of SOTRs, a study of 88 Australian adult CKD and kidney transplant recipients, a clinical-grade wearable device measuring peripheral body temperature with an infrared thermopile correctly identified infection in 65 patients with 80% sensitivity and 98% specificity [27]. Another study found that Bluetooth-enabled devices for at-home physiological monitoring of lung transplant recipients resulted in lower incidences of hospital readmissions [28]. The at-home monitoring consisted of daily updates of BP, HR, weight, blood glucose, SpO 2 , pulmonary function, and activity levels, which could be measured using wearable devices.…”
Section: Wearable Devicesmentioning
confidence: 99%